2017
DOI: 10.1017/jfm.2017.145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of turbulent fluctuations on detonation propagation

Abstract: The present study addresses the reaction zone structure and burning mechanism of unstable detonations. Experiments investigated mainly two-dimensional methane-oxygen cellular detonations in a thin channel geometry. The sufficiently high temporal resolution permitted to determine the PDF of the shock distribution, a power-law with an exponent of -3, and the burning rate of unreacted pockets from their edges -through surface turbulent flames with a speed approximately 3-7 times larger than the laminar one at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 68 publications
(144 reference statements)
3
44
2
Order By: Relevance
“…For the acetylene mixture, the reduction in effective activation energy is 14%, while for propane, the reduction in the activation energy is by 54%! The significantly lower effective activation energy for the much more unstable propane mixture is not surprising, as it was already noted that the enhancement of burning mechanism in turbulent detonations by turbulent mixing suppresses much of the thermal character of the ignition mechanism, where the reaction zone length does not grow with velocity deficit, as anticipated from thermal ignition considerations (Radulescu Maxwell et al 2017). Instead, the rapid burn-out of non-reacted pockets by diffusive processes explains why the reaction zones remain substantially shorter.…”
Section: Effective Reaction Models For Cellular Detonationsmentioning
confidence: 66%
See 2 more Smart Citations
“…For the acetylene mixture, the reduction in effective activation energy is 14%, while for propane, the reduction in the activation energy is by 54%! The significantly lower effective activation energy for the much more unstable propane mixture is not surprising, as it was already noted that the enhancement of burning mechanism in turbulent detonations by turbulent mixing suppresses much of the thermal character of the ignition mechanism, where the reaction zone length does not grow with velocity deficit, as anticipated from thermal ignition considerations (Radulescu Maxwell et al 2017). Instead, the rapid burn-out of non-reacted pockets by diffusive processes explains why the reaction zones remain substantially shorter.…”
Section: Effective Reaction Models For Cellular Detonationsmentioning
confidence: 66%
“…These trends differed fundamentally from experimental observations, where the opposite trend was found, mainly that cellular detonations have an enhanced detonability than anticipated from ZND-type models neglecting the cellular structures, and that more unstable detonations were more detonable than stable ones. It was recently suggested that turbulent mixing in the reaction zone of unstable detonations, absent in the inviscid simulations of the above studies, may account for these discrepancies (Maxwell et al 2017). Indeed, diffusive effects were found to have profound differences even in onedimensional detonation dynamics (Romick et al 2012).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Large-scale vortices involved in the highly unstable shear layers dominate the formation of the turbulent flow and the rapid turbulent mixing between the unburned jet and burned product. Maxwell et al (2017) also showed that for planar detonation propagation in a thin channel, turbulent mixing rates can significantly influence the observed cell patterns and detonation structure. Therefore, to account for diffusion and mixing effects, rather than the commonly known classification of weakly unstable and highly unstable detonations, it should be more appropriate to quantify to which extent the unburned reactant is still present behind the shock front under a specific condition.…”
Section: Viscous Detonationmentioning
confidence: 84%
“…Maxwell et al . (2017) have reported that the triple point is a location of high temperature and pressure due to shock compression from multiple waves as well as a source of enhanced turbulent mixing. These triple points can give rise to slip lines further developing into shear layers that are susceptible to the Kelvin–Helmholtz (KH) instability (Massa, Austin & Jackson 2007), hence acting to enhance the turbulent mixing between the unburned pockets and burned gases (Gamezo, Ogawa & Oran 2007; Oran & Gamezo 2007).…”
Section: Resultsmentioning
confidence: 99%